Green capitalism and distributive justice in the disposal of electro-eletronic residues (Research, Society and Development, 2021)
In the manufacture of electro-electronic devices, various materials are used, especially metals and plastics, with long-term decomposition and high levels of negative impacts on the environment. The aim of this article is to examine, from an interdisciplinary perspective, green capitalism as a management mechanism for the disposal of electronic waste, making a critical analysis of anti-capitalist and non-consumerist practices as methods that reduce policy by programmed obsolescence, as well as Brazilian legislation. and the efforts of international organizations aimed at reducing polluting ecological impacts, linked to industrial production, consumption and poor waste management, in the face of political, economic and social interests. In order to promote a contextualized approach, using an quanti-qualitative methodology, of an investigative and interpretative character, which includes a bibliographic review, through a critical and comparative bias, also examining quantitative information in the most recent productions, in a dialogue between scientific trees, against the background of distributive justice in the theory of justice as equity, by John Rawls (1997) and revisited by Ronald Dworkin (2006), as a social equity, applied to the promotion of the right to the city, proposed by Henry Lefebvre (2001) In the end, a survey considered that the global, social and social dialogues are still incipient, not regarding the disposal of electronic waste, although the recycling of components and parts of the appliance line can be collected and recycled in a more organized way, given that the announced tragedy could have its acts mitigated, through the application of paradigms of justice from the formation of industrial production thinking and techniques.